Learning computer architecture with Raspberry Pi - Upton, Eben; Duntemann, Jeff; Everard, Ben; Davis, Russell (Hoboken, New Jersey : John Wiley & Sons, Inc., 2016)
Use your Raspberry Pi to get smart about computing fundamentals In the 1980s, the tech revolution was kickstarted by a flood of relatively inexpensive, highly programmable computers like the Commodore. Now, a second revolution in computing is beginning with the Raspberry Pi. Learning Computer Architecture with the Raspberry Pi is the premier guide to understanding the components of the most exciting tech product available. Thanks to this book, every Raspberry Pi owner can understand how the computer works and how to access all of its hardware and software capabilities. Now, students, hackers, and casual users alike can discover how computers work with Learning Computer Architecture with the Raspberry Pi. This book explains what each and every hardware component does, how they relate to one another, and how they correspond to the components of other computing systems. You'll also learn how programming works and how the operating system relates to the Raspberry Pi's physical components. -Co-authored by Eben Upton, one of the creators of the Raspberry Pi, this is a companion volume to the Raspberry Pi User Guide -An affordable solution for learning about computer system design considerations and experimenting with low-level programming -Understandable descriptions of the functions of memory storage, Ethernet, cameras, processors, and more -Gain knowledge of computer design and operation in general by exploring the basic structure of the Raspberry Pi The Raspberry Pi was created to bring forth a new generation of computer scientists, developers, and architects who understand the inner workings of the computers that have become essential to our daily lives. Learning Computer Architecture with the Raspberry Pi is your gateway to the world of computer system design.
Enablers and Assistants to the Operating SystemOperating Systems for Raspberry Pi; Chapter 9: Video Codecs and Video Compression; The First Video Codecs; Changing with the Times; Motion Search; Chapter 10: 3D Graphics; A Brief History of 3D Graphics; The OpenGL Graphics Pipeline; Modern Graphics Hardware; Open VG; General Purpose GPUs; Chapter 11: Audio; Can You Hear Me Now?; Analog vs. Digital; Sound and Signal Processing; 1-Bit DAC; I2S; Raspberry Pi Sound Input/Output; Sound on the Raspberry Pi; Chapter 12: Input/Output; Introducing Input/Output; I/O Enablers; Raspberry Pi GPIO
Description based on CIP data; item not viewed.
Keywords: Raspberry Pi (Computer); Computer architecture; Electronic books